Efektivitas Program Kota Tanpa Kumuh di Kelurahan Sukamare Kota Palembang - Aprianti, Nisa; Sulastri, Sri; Asteriniah, Femi (@-Publik: Jurnal Administrasi Publik, 2024)
The purpose of this study is to analyze the Implementation of Limited Face-to-Face Learning in Physical Education Subjects for Sports and Health at the State Elementary School Level Cluster III, Pemulutan District, Ogan Ilir Regency. The method used is a qualitative descriptive analysis technique. The results of the study revealed that Face-to-Face Learning Limited to Physical Education Subjects for Sports and Health at the State Elementary School Level Cluster III, Pemulutan District, Ogan Ilir Regency, has been carried out well. This can be seen based on the Analysis of Limited Face-to-Face Learning in Physical Education Subjects sports and health at the State Elementary School Level Cluster III Pemulutan District, Ogan Ilir Regency which includes the dimensions and indicators used, namely: Planning (Limited NCD Implementation Requirements; HR preparation; Preparation of Infrastructure); Organizing (Organizational Structure; Division of duties and responsibilities); Implementation (Implementation of Health Protocols; Learning Activities); Supervision (Supervision and control; Evaluation and reporting) all of which have been carried out well. It is necessary to increase the learning time in PJOK Subjects so that teachers can manage learning so as to allow teachers to meet the load of teaching hours and achieve curriculum completion; It is necessary to improve the ability of teachers to manage two classes with different models, such as face-to-face (offline) and at home (online), teachers must be able to prepare materials and teaching methods well and must be able to use appropriate methods in the learning and teaching process so that it will make it easier to provide understanding to students who follow the subjects given.